Outcome of umbilical cord prolapse at Aminu Kano Teaching Hospital, Kano, North-Western Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Prolapse of the umbilical cord is an obstetric emergency with life-threatening effect on the foetus. The outcome of umbilical cord prolapse (UCP) depends on immediate and proper interventions.Objectives:To determine the incidence of cord prolapse, predisposing factors, foetal outcome and decision-delivery interval in emergency caesarean section (c/s) due to cord prolapse in our Teaching Hospital.Materials and Methods:A retrospective review of 42 consecutive cases of UCP over a 5-year period was conducted at Aminu Kano Teaching Hospital, Kano, in North-Western Nigeria.Results:There were 42 cases of cord prolapse out of 13,292 deliveries during the study period giving an incidence of 0.32% or 1 in 316 deliveries. The highest incidence occurred in women aged 25-34 years. Multiparous women constituted 76.2% of the patients. Prematurity was the highest contributing factor (47.6%). Twenty-five (59.2%) of the 42 patients had emergency c/s (1.41% of the 1,771 emergency c/s and 0.99% of a total of 2,053 c/s). The mean decision to delivery interval in patients who had c/s was 92.8 minutes (range 10-180 minutes). The mean birth-weight was 2,864 g. The mean Apgar score at 5 minutes was 5.2. There were 19 fresh stillbirths with perinatal mortality of 45.2%.Conclusion:Cord prolapse is relatively uncommon in our environment. There is the need to identify and educate those women at increased risk of their babies having UCP. Delay in presentation may have contributed to the high perinatal mortality. Smooth organisation of an emergency c/s is essential for rapid and safe management of patients with UCP.